Using genetic diversity in deep root systems of forage grasses and rice to capture carbon in tropical soils - Arango, Jacobo; Villegas, Daniel Mauricio; Jauregui, Rosa; Cardoso, Juan Andrés; Costa, Ciniro; Rebolledo, Camila; Álvarez, María F.; Selvaraj, Michael; Rodríguez, Leonardo; Mayorga, Mildred; Chavarriaga Aguirre, Paul; Notenbaert, An Maria Omer; et al. (International Grassland Congress 2023, 2023)
Agricultural soils have the potential not only to be sinks of carbon dioxide (CO2) but also to mitigate the emissions of this gas to the atmosphere, thus, alleviating global warming. Perennial tropical grasses and rice upland and lowland varieties exhibit a large untapped genetic diversity in their root systems (e.g., deep rooting ability, exudation rates and chemical composition) that, if unlocked, could contribute to increased food production in crop-livestock systems while enhancing soil organic carbon (SOC) in tropical regions. Nature based solutions that improve crop adaptation and SOC storage in tropical soils could help to remove CO2 from the atmosphere and thereby benefit the global climate system. With the launch of Future Seeds, one of the world’s largest repositories of tropical crop varieties, the Bezos Earth Fund (BEF) granted a major project within the Program of Future of Food. The focus of this BEF funded project is to: (i) develop novel high throughput phenotyping methods to evaluate genetic diversity of root systems of tropical grasses and rice; (ii) unravel the potential of root systems in crop-livestock systems to replenish soil organic carbon (SOC) in human-intervened areas in tropical soils; (iii) identify and target hotspots/agroecological niches for SOC storage in tropical soils; and (iv) build capacity in conducting research on root systems and SOC storage towards carbon farming in tropical regions. Implementation of land-based SOC storage practices/projects (through carbon markets) based on deep rooting ability of perennial tropical forage grasses and rice cultivars in crop-pasture rotational systems could significantly reduce net emissions from tropical soils.